Non-invasive tissue oximetry following unilateral DIEP-flap reconstruction: A pilot evaluation. (June 2017) - Vranken, N.P.A.; Weerwind, P.W.; van Onna, M.A.; Bouman, E.A.C.; van der Hulst, R.R.W.J.
Abstract: Introduction: Post-operative monitoring of a free flap transplant in the form of a deep inferior epigastric perforator flap (DIEP-flap) is crucial for early detection of vascular compromise. The aim of the current study, therefore, is to gain insight whether non-invasive tissue oximetry is suitable for the assessment of tissue perfusion following DIEP-flap surgery and whether it can serve as an early marker for vascular compromise. Methods: Patients (n = 29) undergoing secondary unilateral DIEP-flap surgery were included in this prospective explorative study. Non-invasive tissue oxygen saturation (StO2 ) measurements were performed using one sensor positioned on the DIEP-flap and another positioned on the native breast. Measurements were performed directly after the surgical procedure until 24 h post-operatively. Results: Tissue oxygenation response was swift in the native breast (on average 11.9%/h for 84 min, n = 28), whereas the DIEP-flap showed a lower and more extended tissue recovery phase of approximately 7.5%/h for 6 h (n = 23). In some of these latter cases (n = 14), an acute and second more prolonged response was observed in the DIEP-flap. The average difference between the DIEP-flap and native breast StO2 was 4% across the entire measurement (p = 0.043). Two patients underwent post-operative re-exploration of the DIEP-flap, in which an immediate and constant enlarged difference between DIEP-flap and native breast StO2 (≥38%) and a decreased DIEP-flap StO2 (≤43%) was observed. Conclusion: Continuous non-invasive tissue oxygen saturation is suitable for postoperative monitoring of DIEP-flaps, and StO2 pattern may aid in early identification of vascular compromise in DIEP-flaps.